Utilisation of Herbicide Reductant to Improve Weed Control in Oil Palm Plantations - Kamalul Adham, Che Ruzlan; Tan, Choon Chek; Muhammad Saiful, Ahmad Hamdani; Muhamed Ramdhan, Ab Latiff; Cik Mohd Rizuan, Zainal Abidin; Noor Hisham, Hamid (2023)
A well considered weed management strategy has to strike a balance in terms of crop and weed competition, crop injury, efficient cost of control measures, impact on the environment, and the need to reduce soil erosion, especially in the tropics with high and intense rainfall Furthermore, weeds must be managed efficiently with an acceptable cost to ensure crop profitability. Therefore, FGV has conducted a series of studies on Weed Solut ion 2 sodium amine or 2 SA), a novelty herbicide reductant product to be mixed with any herbicide and claimed to reduce its effective herbicide dosage by up to 50 70 The 2 SA is categorized as inorganic salts adjuvant, with additives that aim to improve the efficiency of herbicides A series of experiments was conducted in immature and mature oil palm at Ladang FGV Agri Services, Jerantut, Pahang to verify the claims Addition of 2 SA herbicide reductant successfully reduced chemical herbicide dosage by 50 for circle weeding in immature oil palm, and by 70 for inter row weeding (broad leaves) and selective weed control of Clidemia hirta In mature palms, the reduced herbicide doses with 2 SA gave similar weed control efficacy with the standard practice 100 herbicide only) Cost savings of overall herbicides used per ha per round of 14 to 25 were achieved compared to the standard treatments without 2 SA Moreover, 2 SA did not show any phytotoxic effect on oil palm at 6 weeks after spraying at 0 5 1 0 and 1 5 L/ha of the mixtures These findings attest to the cost effectiveness and product safety of 2 SA towards effective weed management and improve sustainability of oil palm plantations.